Bird communities and seedling recruitment in restoring seasonally dry forest using the framework species method in Northern Thailand - Chawapich Wydhayagarn (2018)
This study examined the effects of framework trees, planted in 1998, and bird community on the natural recruitment of tree seedling species in a forest restoration experiment designed to test the framework species method of forest restoration established by Chiang Mai University's Forest Restoration Research Unit (FORRU-CMU). Tree seedlings establishing beneath five framework tree species: Erythrina subumbrans (Hassk.) Merr., Hovenia dulcis Thunb., Melia toosendan Sieb. & Zucc., Prunus cerasoides D.Don and Spondias axillaries Roxb., were surveyed. Five trees of each species were selected in the 8-year-old trial plots. Birds visiting each tree were observed to determine possible seed dispersal activities. Thirty-six tree seedling species were found beneath the selected trees, of which 11 were wind-dispersed and 25 were animal-dispersed. The population density of animal-dispersed tree seedlings was higher than the wind-dispersed seedlings beneath all selected framework trees. The sample plots beneath P. cerasoides supported the highest population density of tree seedlings. Forty-nine bird species were recorded visiting the framework trees between July 2006 and June 2007. Non-frugivorous birds were recorded more frequently than the frugivorous birds. The effects of birds on seedling recruitment were different among each of the selected framework tree. Bigger trees, which attracted high number of birds by providing food resources, roosting and nesting sites may increase the seed deposition more than smaller trees with fewer attractants. © 2009 Springer Science+Business Media B.V.